Play-Based Learning as a Pedagogical Approach to Promote Islamic Values in Early Childhood Education - Adeoye, Moses Adeleke; Alahmari, Sarah A. (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
This research article explores the integration of play-based learning and Islamic values in early childhood education, aiming to understand how playful experiences can enhance moral and social development in young learners. Employing a systematic literature review methodology, the study synthesises findings from various scholarly articles to identify key themes and effective teaching strategies. The significant findings reveal that play serves as a crucial medium for developing moral values, social skills, cognitive abilities, and cultural awareness among children. Specifically, play-based activities foster empathy, cooperation, and critical thinking while promoting respect for diversity. Effective strategies such as storytelling, role play, cooperative games, and creative expression are highlighted as valuable methods for teaching Islamic values. In conclusion, integrating play-based learning with Islamic values education offers a holistic approach to nurturing well-rounded individuals. This research contributes to the existing body of knowledge by providing a comprehensive overview of how play can instil ethical principles and foster social responsibility in early childhood settings. By emphasising the importance of play in moral development, this study encourages educators to adopt innovative practices that align with educational and cultural objectives, ultimately preparing children for compassionate and responsible participation in society.